Efeito da espessura e do material restaurador na resistência à fratura de facetas oclusais confeccionadas em CAD/CAM - Andrade, Jonas Pereira (2017)
The aim of the study was to evaluate, in vitro, the fracture resistance of occlusal veneers, made by CAD/CAM, with Lava Ultimate, e.max CAD and Vita Enamic materials in thicknesses of 0.6 mm and 1.5 mm. Seventy third human sound molars were randomly divided into seven groups (n = 10) according to the variables material and thickness, with the sound teeth as control. The root of the teeth was embedded into a self-cured acrylic resin and the teeth were prepared to simulate advanced erosion of the occlusal surface. The occlusal veneers were made using CAD-CAM technology, being luted to the preparation with adhesive systems and resin cements. After storage in distilled water at 37 °C for 24 h, the samples were submitted to mechanical cyclic loading (1 million cycles at 100 N load). Subsequently, the sound teeth and the samples with the occlusal veneers were submitted to the fracture resistance test in a universal testing machine with crosshead speed of 1 mm/min. The failures were classified as reparable and irreparable. According to two-way ANOVA, the interaction between material and thickness was significant (p=0.013). The highest fracture resistance was obtained for the e.max CAD in the thickness of 1.5 mm (4995 N), being statistically superior to the other groups (p <0.05). The lowest fracture resistance was obtained for Vita Enamic at 0.6 mm thickness (2973 N), not being significantly different from e.max CAD 0.6 mm (3067 N), Lava Ultimate 0.6 mm (3384 N), Vita Enamic 1.5 mm (3540 N) and Lava Ultimate 1.5 mm (3584 N) (p>0.05). According to one- way ANOVA, the fracture resistance of the sound teeth (3991 N) did not differ significantly from the teeth with occlusal veneers (p> 0.05). The failures were predominantly repairable, except for sound teeth and Lava Ultimate 1.5 mm. The Lava Ultimate, e.max CAD and Vita Enamic occlusal veneers, in the thicknesses of 0.6 mm and 1.5 mm, showed fracture resistance exceeding the maximum masticatory forces.